Các hợp chất flavonoit và lignan từ cây chó đẻ thân xanh Phyllanthus amarus. - Tuấn, Trần Anh; Thái, Trần Huy; Hưng, Nguyễn Quang; Đạt, Nguyễn Tiến; Nam, Nguyễn Hoài; Minh, Châu Văn; Kiệm, Phan Văn (Vietnam Journal of Chemistry, 2012)
The plant Phyllanthus amarus has been used for a long time in Vietnamese traditional medicine as diuretic, antiseptic agent and for treatment of pimple and snack bite. In our continuing study on the chemical constituent and biological activity of medicinal plants, a phytochemical investigation of the methanol extract of Phyllanthus amarus led to the isolation of seven known compounds as quercetin (1), astragalin (2), quercitrin (3), isoquercitrin (4), pinoresinol (5), syringaresinol (6), and hydrophyllanthin (7). Their structures were identified by spectroscopic methods including ESI-MS, 1D- and 2D-NMR in comparison with the literature.